FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN SISTEM INFORMASI BERBASIS KOMPUTER DENGAN GENDER SEBAGAI VARIABEL MODERATING - Novianti, Nurlita; Baridwan, Zaki (Universitas Brawijaya, 2010)
The objectives of the research is to examine some factors that influence intention of utilization ofÂ computer based information system and gender as moderating variable by using Unified Theory of Acceptance and Use of Technology (UTAUT)Â framework that proposed by Venkates et al., (2003). This research was conducted in public sector organizations in Malang on information system and information system usage. There were 65 respondents involved. The data was analyzed by using multiple regression and moderating regression analysis by SPSS 13 software. The result indicates that simultaneously, the performance expectancy, effort expectancy, and social factor significantly influence the intention of utilization of computer based information system. It might be concluded that the intention of utilization of computer based information system is influenced by social factor. Further-more, the analysis result also indicates that gender is not significant as moderating variable from performance expectancy, effort expectancy, and social factor. The implication of the research is relevant toward public sector organizations which adopt and advance information system in its operationalities, to consider factors which influence the intention of utilization of computer based information system.